PENGARUH CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) (Studi Empiris pada Perusahaan Non Keuangan yang terdaftar di Bursa Efek Indonesia Tahun 2015 - 2021 - Sirait, Kevin Nicholas; Fuad, Fuad (Diponegoro Journal of Accounting, 2024)
This study aims to test and find empirical evidence of the effect of corporate governance on ESG disclosure. The corporate governance attributes include institutional ownership, board size, gender diversity, proportion of independent commissioners, and size of the committee audit. The control variables in this study include firm size, leverage, and profitability. The Bloomberg database's ESG rating serves as a measure of the dependent variable, ESG disclosures. The population of this study uses non-financial companies listed on the IDX from 2015 to 2021. Total sample use amounted to 545, which was determined through purposive sampling with various criteria. The analysis method used is panel data regression, considering the number of companies and years of observation used in this study. The results of this study show that the proportion of independent commissioners has a positive effect on ESG, and institutional ownership has a negative effect on ESG. Meanwhile, other attributes have no relationship to ESG disclosure.